2011
DOI: 10.1073/pnas.1013965108
|View full text |Cite
|
Sign up to set email alerts
|

Myelination transition zone astrocytes are constitutively phagocytic and have synuclein dependent reactivity in glaucoma

Abstract: Optic nerve head (ONH) astrocytes have been proposed to play both protective and deleterious roles in glaucoma. We now show that, within the postlaminar ONH myelination transition zone (MTZ), there are astrocytes that normally express Mac-2 (also known as Lgals3 or galectin-3), a gene typically expressed only in phagocytic cells. Surprisingly, even in healthy mice, MTZ and other ONH astrocytes constitutive internalize large axonal evulsions that contain whole organelles. In mouse glaucoma models, MTZ astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
185
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(199 citation statements)
references
References 39 publications
11
185
1
2
Order By: Relevance
“…Both phagocytosis and cell infiltration are implicated in glaucoma (5,41,64,65). Given the physiological function of ONH astrocytes in phagocytosing myelin and mitochondria, an early effect of high IOP may be to alter astrogliosis and disrupt phagocytosis (41,66). These functions are carried out when C3 effector fragments bind various receptors, including C3AR1 for C3a and CR1, CR2, CR3, and CR4 for C3b (67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both phagocytosis and cell infiltration are implicated in glaucoma (5,41,64,65). Given the physiological function of ONH astrocytes in phagocytosing myelin and mitochondria, an early effect of high IOP may be to alter astrogliosis and disrupt phagocytosis (41,66). These functions are carried out when C3 effector fragments bind various receptors, including C3AR1 for C3a and CR1, CR2, CR3, and CR4 for C3b (67).…”
Section: Discussionmentioning
confidence: 99%
“…Other functions of C3 include promoting phagocytosis, cell adhesion, and chemotaxis. Both phagocytosis and cell infiltration are implicated in glaucoma (5,41,64,65). Given the physiological function of ONH astrocytes in phagocytosing myelin and mitochondria, an early effect of high IOP may be to alter astrogliosis and disrupt phagocytosis (41,66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we described a phenomenon at the optic nerve head (ONH) of WT mice, where evulsions originating from otherwise intact axons are engulfed and degraded by resident phagocytic astrocytes (4). Serial section-based 3D reconstructions obtained through serial block-face scanning electron microscopy (SBEM) revealed that the protrusions on axons and the evulsions near axons were common throughout the ONH in both the glial lamina, where retinal ganglion cell axons are unmyelinated, and in the adjacent myelination transition zone (MTZ).…”
mentioning
confidence: 99%
“…One recent glaucoma hypothesis posits that phagocytic astrocytes in a particular region of the optic nerve, an area just rostral to the beginning of myelination (the myelination transition zone, or MTZ), become dysregulated. These phagocytic MTZ astrocytes express Mac-2 and upregulate it with IOP increase; the Mac-2 levels correlated with the number of RGCs with damaged axons in the retina (Nguyen et al, 2011). Spheroids in the MTZ contained -synuclein; their numbers increased in DBA/2J mice with glaucoma.…”
Section: On Astrocytesmentioning
confidence: 99%